2019
DOI: 10.3389/fnhum.2019.00164
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Based Classification of Resting-State fMRI Features Exemplified by Metabolic State (Hunger/Satiety)

Abstract: Objective Resting-state functional magnetic resonance imaging (rs-fMRI) has become an essential measure to investigate the human brain’s spontaneous activity and intrinsic functional connectivity. Several studies including our own previous work have shown that the brain controls the regulation of energy expenditure and food intake behavior. Accordingly, we expected different metabolic states to influence connectivity and activity patterns in neuronal networks. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 120 publications
0
23
0
Order By: Relevance
“…Since then, the subsequent studies on brain function using resting-state fMRI (rs-fMRI) data has exploded. For example, recent studies have shown that rs-fMRI has become an essential technique to analyze the brain's spontaneous activity and intrinsic functional connectivity [3].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the subsequent studies on brain function using resting-state fMRI (rs-fMRI) data has exploded. For example, recent studies have shown that rs-fMRI has become an essential technique to analyze the brain's spontaneous activity and intrinsic functional connectivity [3].…”
Section: Introductionmentioning
confidence: 99%
“…This method was used to extract optimal features from functional MRI (fMRI) connectivity matrix graph measures, and the features were feed into SVM for classification. Al-Zubaidi et al had a similar result in classifying human with metabolic states (hunger/satiety) [22]. The extracted connectivity parameters from 90 brain regions and used sequential forward floating selection strategy with linear SVM to classify the human with the two states.…”
Section: Multivariate Analysis Methods Introduced Machine Learningmentioning
confidence: 93%
“…Sets C and D contained only seizure-free activity, while set E was the only one that contained seizure activity. In this paper, the full set of the datasets (i.e., A,B,C, D and E) were used, like in [11,12]. Unlike the start/plus fMRI dataset, the dataset for the epilepsy prediction problem has large number of samples (the actual size of the full dataset is 11,501) to train and test for deriving the best prediction problem.…”
Section: Further Analysis Of the Vwm-based Features For Epileptic mentioning
confidence: 99%
“…To improve the analysis of brain diseases, a framework that was proposed in [10] utilizes fMRI data to estimate the states and parameters of the stochastic Metabolic Hemodynamic Model (sMHM). A recent research work [11] investigated the influence of hunger and satiety on rs-fMRI using three connectivity models namely; local connectivity, global connectivity and amplitude rs-fMRI signals.…”
Section: Introductionmentioning
confidence: 99%